Tracing the Source of Fermenting Microbiota in Pickled Chinese Cabbage Based on Endophytic Bacteria Analysis - ZHANG Qingfang, CHEN Wenli, WU Jiaming, ZHAO Lu, MA Minghao, WANG Xiaohui, CHI Naiyu (Shipin Kexue)
In order to explore the source of fermenting microorganisms in pickled Chinese cabbage, this study used high-throughput sequencing and bioinformatics techniques to investigate the diversity of microbial community in the fermented juices of raw and cooked Chinese cabbage at the early stage of fermentation and the diversity of total and culturable endophytic bacteria in Chinese cabbage. The results showed that at the phylum level, most of the bacteria in the fermented juices of raw and cooked Chinese cabbage were the same as the endophytic bacteria of Chinese cabbage. Four lactic acid bacteria genera were annotated in each of the fermented juices, namely Lactococcus, Leuconostoc, Lactobacillus, and Weissella, and 299 genera including 6 lactic acid bacteria genera were annotated in the endophytic bacteria. The lactic acid bacteria genera induced four ones common to both fermented juices as well as Bifidobacterium and Tetragenococcus, indicating that the endophytic bacteria were one of the sources of lactic acid bacteria in pickled Chinese cabbage. Compared with pickled raw Chinese cabbage, the number and relative abundance of pathogenic bacteria genera annotated in pickled cooked Chinese cabbage were significantly reduced, and most of the pathogenic bacteria genera detected belonged to the pathogenic endophytic bacteria genera in Chinese cabbage. Among the 51 culturable endophytic bacterial genera identified on plates, three lactic acid bacteria genera were also found in pickled Chinese cabbage.